Mechanical evaluation of a novel resin infiltrated lithium-disilicate ceramic network versus resin infiltrated feldspathic ceramic network - Mariam Adel; Moustafa Aboushlieb; Nour A. Habib (Discover Applied Sciences)
Abstract Mechanical properties of polymer infiltrated ceramic network (PICN) fall in range between that of resin-based composites and glass ceramics. The aim of this study was to evaluate the mechanical properties of a newly fabricated polymer infiltrated lithium-disilicate network (PILN) and compare it with the commercially available PICN whose ceramic network is feldspathic ceramic (Vita Enamic, Vita Zahnfabrik, Bad Säckingen, Germany). Commercially available lithium disilicate based glass–ceramic CAD/CAM blocks (IPSe.max, Ivoclar, Schaan, Liechtenstien) were ground into a fine powder and used to produce a porous ceramic network (25% porosity). Resin was infiltrated and polymerized to form a dense PILN. Porosity percentage and microstructure were investigated. Single crowns were milled from the newly fabricated PILN blocks and from Vita Enamic then fracture load test was performed. Rectangular specimens were prepared from both materials, afterwards, flexural strength, fracture toughness, brittleness and Vickers’ hardness tests were investigated. Data were analyzed using independent sample-t test and paired sample-t test (n = 12, α = 0.05). Results showed that newly formulated PILN had significantly higher fracture resistance (1640 N) and superior fracture toughness (2.6 MPa m1/2) compared to the control which showed (1103 N) fracture load and (1.7 MPa m1/2) fracture toughness. PILN had lower brittleness index (0.89 μm1/2) than Vita Enamic (1.48 μm1/2) reflecting superior milling qualities. It was concluded that newly fabricated PILN material showed enhanced mechanical properties.